A proposed selection process in Over-The-Top project portfolio management - Jemy Vestius Confido; Dermawan Wibisono; Yos Sunitiyoso (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The purpose of this paper is to propose an Over-The-Top (OTT) initiative selection process for communication service providers (CSPs) entering an OTT business. Design/methodology/approach: To achieve this objective, a literature review was conducted to comprehend the past and current practices of the project (or initiative) selection process as mainly suggested in project portfolio management (PPM). This literature was compared with specific situations and the needs of CSPs when constructing an OTT portfolio. Based on the contrast between the conventional project selection process and specific OTT characteristics, a different selection process is developed and tested using group model-building (GMB), which involved an in-depth interview, a questionnaire and a focus group discussion (FGD). Findings: The paper recommends five distinct steps for CSPs to construct an OTT initiative portfolio: candidate list of OTT initiatives, interdependency diagram, evaluation of all interdependent OTT initiatives, evaluation of all non-interdependent OTT initiatives and optimal portfolio of OTT initiatives. Research limitations/implications: The research is empirical, and various OTT services are implemented; the conclusion is derived only from one CSP, which operates as a group. Generalization of this approach will require further empirical tests on different CSPs, OTT players or any firms performing portfolio selection with a degree of interdependency among the projects. Practical implications: Having considered interdependency, the proposed OTT initiative selection steps can be further implemented by portfolio managers for more effective OTT initiative portfolio construction. Originality/value: While the previous literature and common practices suggest ensuring the benefits (mainly financial) of individual projects, this research accords higher priority to the success of the overall OTT initiative portfolio and recommends that an evaluation of the overall portfolio should occur prior to individual evaluation. Consequently, certain initiatives may not provide direct individual benefits. Those initiatives should remain within the portfolio because they are needed for the success of other initiatives.
Keywords: 650; communication service provider (CSP); over-the-top (OTT) initiative; interdependency; project portfolio management